Caracterización de sistemas de producción lechera y salud de la ubre en el norte de Antioquia, Colombia (2024)
ABSTRACT: Background: The sociodemographic characterization of milk producers allows knowing their particular conditions in terms of social, political and economic structure through indicators that describe them as social actors, interaction networks, conflict situations and events related to milk production. Objective: To characterize the diversity of dairy production systems in Northern Antioquia with a focus on the producer, the farms, access to services and their impact on the biological indicators of udder health. Methodology: A cross-sectional study was designed that including 216 milk producers within distributed in 9 dairy municipalities in northern Antioquia. Surveys to characterize the producer, the farm and access to services for health and milk production were carried out. As biological indicators of udder health, the annual averages of bulk tank somatic cell counts (BTSCC) and colony-forming units (CFU) of each farm were analyzed. Statistical analyzes were performed with SPSS version 25.0 and a p < 0.05. Results: The biological indicators of udder health in the studied farms presented poor sanitary quality according to the BTSCC for 67 % of the producers and poor hygienic quality with CFU in for 22 % of the participating farms. Briceño producers showed the lowest production in contrast to Santa Rosa de Osos milk producers, who have the highest production. In the linear regression models, 18.2 % of the BTSCC was explained by the location in relation to the municipality, the size of the production system and the type of milking. The CFU values were explained in 29.8 % by the municipality, the cooperative association or livestock association, the milk storage system, the offer of laboratory services for milk and cows, the area of the farm dedicated to grazing, the number of animals on the farm and the average daily production per cow. Implications: This study shows the importance of understanding udder health issues not only at the cow level from a biomedical approach. The understanding of udder health from the farm in the sociodemographic context shows that its location, access to services, technology, education and associativity establish opportunities to improve production and competitiveness of milk production. Conclusions: udder health can be positively or negatively affected by the location of the production system, the size of the production system, the type of milking, the association to a cooperative or livestock association, the milk storage system, the supply of laboratory services for milk and cows, the area of the farm dedicated to grazing, the number of animals on the farm and the average daily production per cow. To consider these variables is fundamental in decision-making in mastitis control and preventive care for udder health.